Penggunaan Teknik Bibliokonseling Berbantuan Happines In Jar pada Siswa yang Mengalami Afeksi Negatif - Tiara, Tiara Anggun Mauladi; Sahril Buchori; Akhmad Harum (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
This study examines the use of Bibliocounseling techniques with the help of Happines in jar on students who experience negative affection at SMP Negeri 30 Makassar. With the aim of the study to find out the use of Bibliocounseling techniques with the help of Happines in jar can reduce the negative affection of students at SMP Negeri 30 Makassar. The method used in this research is Quantitative with the type of research Quasi Experiment, with a non-equivalent control group design. The population in this study were 17 students who were identified as having high negative affection, so the sample in this study were 12 students with the determination of the sample using proportional random sampling technique. The data collection techniques used are questionnaires, observation, and documentation. Data analysis using descriptive analysis and inferential statistical analysis using SPSS v.25. The results showed that: The use of bibliocounseling techniques with the help of Happines in jar can reduce the negative affection of students at SMP Negeri 30 Makassar, this can be seen from the results of calculations through the independent samples t test obtained sig value. (2- tailed) = 0.019 which means smaller than <0.05 thus H0 is rejected and H1 is accepted. So it can be concluded that the Bibliocounseling technique with the help of Happines in jar can reduce the negative affection of students at SMP Negeri 30 Makassar.